Efecto de la fertilización con N,K,S, sobre el rendimiento del híbrido de maíz (Zea mays L.) INIAP-H-553, en la zona central del Litoral Ecuatoriano. - Betancourt Ching, Rolando Damian (2011)
This research was realized during the rainy season in 2009 – 2010 in the Ecuadorian Coastal Region during the Dry – Rainy stage the place is located in the Tropical Experimental Station “Pichilingue” of INIAP, which is in the Km. 5 Via Quevedo El Empalme in the Los Rios Province; The objective were to determine: * To know the appropriate dosis ofin the hybrid N, K, S to obtain the best yield on corn INIAP H – 553 * To analyze economically the studied treatments according to the efficiency and production costs. The area corresponds to the humid Tropical weather; witch a precipitation about 2252 mm, temperature per year is 24.5 ºC, average relative humidity 84% heliophany 719.40 hours sun per year. It is land is composing of rocks, and a flat topography. The treatments were design on full bricks witch a factorial fix of: A (5) * B (4) + 3 witch four repetitive y receipts. The values between its treatments will be compared by using Tuckey is law 0.5% of probabilities. This application doesn’t meaningless evolve: grains or the mazorca. Latitude plus its production equals 4.6 kg (rainy season), and 7.02 kg (dry season). Sulfate is dosis has a better effect on corn is harvest. This application consists of 66 kgha-1 in every study that varies. This dosis gets all corn – cob a better diameter, better percentage of well – treated corn – cob, with better growth. Every time nitrogen was applied on rainy or dry season. The difference that farmers had, when it comes down to its harvest was superior than without or previous. The increments of 12.08 and 10.3 kg of N applied in every dry pr raing season. The best answer for the N application is 138 kg/ha-1dosis in rainy season. The diameter, percentage of well – treated corn – cob is beyond great. However on the dry season, the best harvest happens when 207 kgha-1.